Truth or fake news? The dilemmas and vulnerability of modern society to misinformation: Array - Mireanu, Constantin (Acta Universitatis Danubius. Communicatio, 2022)
We live in times that know an unprecedented flow of information, mediated by the new technological environment. Information can be created and disseminated by any account holder on a social network, who has a smart device at hand connected to the Internet. In this informational noise one acts based on emotions, decisions are made based on false data, chaos and uncertainty are sometimes created, especially in crisis situations. Fake news, these complex constructs that mix false information with truthful ones in doses that make them more and more credible, have become words used in any context, either to sometimes discredit concrete decisions or actions, beneficial to society, or to blame dishonest actions, taken with a well-targeted purpose. The phenomenon has effects in any situation, sometimes immediate, such as incitement to violence, protests, etc., some other times in the long run, such as reduced trust in research, in science, in state institutions, in the political class, etc.